2007
DOI: 10.1002/gps.1872
|View full text |Cite
|
Sign up to set email alerts
|

Vascular disease and apathy in old age. The Leiden 85‐plus Study

Abstract: In community dwelling elderly, those with vascular disease were at higher risk of developing apathy but not depression. This suggests that apathy and depression in old age have different etiologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
154
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(172 citation statements)
references
References 40 publications
14
154
4
Order By: Relevance
“…[15]. In a factor analysis of the GDS-15, these 3 items loaded on the same factor [16]. We recently confirmed this factor analysis of the GDS-15 in a cohort of 3,534 elderly, in which we also confirmed the clinical applicability of the GDS-3-apathy [17].…”
Section: Apathy and Depression Assessmentsupporting
confidence: 71%
See 2 more Smart Citations
“…[15]. In a factor analysis of the GDS-15, these 3 items loaded on the same factor [16]. We recently confirmed this factor analysis of the GDS-15 in a cohort of 3,534 elderly, in which we also confirmed the clinical applicability of the GDS-3-apathy [17].…”
Section: Apathy and Depression Assessmentsupporting
confidence: 71%
“…We recently confirmed this factor analysis of the GDS-15 in a cohort of 3,534 elderly, in which we also confirmed the clinical applicability of the GDS-3-apathy [17]. The test characteristics of this GDS-3-apathy have been shown to be good compared to the 14-item apathy scale of Starkstein, with a sensitivity of 69% and a specificity of 85% [16,18]. The remaining items reflect general depressive affect and life satisfaction, which we will refer to as symptoms of depressive affect [15].…”
Section: Apathy and Depression Assessmentsupporting
confidence: 66%
See 1 more Smart Citation
“…It has been reported that up to a quarter of nondemented community-dwelling elderly individuals have apathy (most without concomitant depression) [50,51]. In this population a past history of stroke (OR 1.8; 95% CI 1.4–2.3) [50] or other vascular diseases are risk factors for apathy [51]. The prevalence of apathy is significantly higher in demented patients [52].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, apathy was associated with cognitive and functional impairments in elders adjudged to have normal cognition [48]. It has been reported that up to a quarter of nondemented community-dwelling elderly individuals have apathy (most without concomitant depression) [50,51]. In this population a past history of stroke (OR 1.8; 95% CI 1.4–2.3) [50] or other vascular diseases are risk factors for apathy [51].…”
Section: Discussionmentioning
confidence: 99%